2022
DOI: 10.32585/ags.v6i1.2392
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kemasan Edible Film Dari Tepung Gathot (Singkong Terfermentasi) Terhadap Karakteristik Kimiawi Sosis Ayam Di Suhu Ruang

Abstract: Tujuan penelitian ini untuk mengetahui perubahan secara kimiawi dari sosis ayam dengan kemasan edible film tepung gathot selama penyimpanan 8 hari di suhu ruang. Materi yang digunakan adalah gathot kering, karagenan dan gliserol. Metode dilakukan secara eksperimen, uji kimiawi sosis ayam dianalisis secara kuantitatif RAL pola faktorial 2x5, faktor pertama yaitu jenis edible film (0,00 dan 0,75%) dan faktor kedua yaitu lama penyimpanan (0; 2; 4; 6; 8 hari), dengan masing-masing 4 kali pengulangan. Data kuantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The edible coating used has a certain density so that the availability of oxygen on the surface of the sausage is reduced [25]. Ratnaduhita and Wianto [26] reported that chicken sausages coated with cassava flour-based edible film were better able to withstand the rate of oxidation compared to sausages without edible coating.…”
Section: Free Fatty Acidmentioning
confidence: 99%
“…The edible coating used has a certain density so that the availability of oxygen on the surface of the sausage is reduced [25]. Ratnaduhita and Wianto [26] reported that chicken sausages coated with cassava flour-based edible film were better able to withstand the rate of oxidation compared to sausages without edible coating.…”
Section: Free Fatty Acidmentioning
confidence: 99%